Increased interleukin-35 expression in tumor-infiltrating lymphocytes correlates with poor prognosis in patients with breast cancer. (January 2017) - Zhao, Zhonghua; Chen, Xi; Hao, Shengnan; Jia, Rui; Wang, Nana; Chen, Shaoshui; Li, Mianli; Wang, Chuanxin; Mao, Haiting
Highlights: IL-35 is expressed in tumor-infiltrating lymphocytes of breast cancer. The expression level of IL-35 in TILs may be a valuable prognostic factor for IDC. High plasma IL-35 levels were associated with late TNM stage in IDC. Increased IL-35 + populations in the TILs may impair antitumor immune response. Abstract: Interleukin-35 (IL-35) is a recently discovered inhibitory cytokine, which is firstly discovered to be produced by regulatory T cells (Tregs) and proposed as a key effector molecule of Treg function. This study aims to analyze the correlation between IL-35 expression in tumor-infiltrating lymphocytes (TILs) of breast cancer tissue and patients' clinical characteristics. Plasma IL-35 was also determined in 60 patients with breast invasive ductal carcinoma (IDC) and 30 healthy women by enzyme-linked immunosorbent assay. IL-35 expression in the tissue specimens was analyzed by immunohistochemistry. It was shown that 39.1%, 43.6% and 17.3% of the 110 patients were absent, weak, and strong IL-35 expression in the TILs, respectively. Strong IL-35 expression in TILs was significantly associated with age >50 years, tumor size >2 cm, TNM stage III, and negative ER (All P < 0.05). Patients with elevated IL-35 expression in TILs had significantly worse progression-free survival (PFS) and overall survival (OS) than patients with weak or no IL-35 expression (All P  < 0.05). High plasma IL-35 levels were significantly associated with TNM stage III and lymph node metastasis (All P  < 0.05). Plasma IL-35 level and IL-35 expression in the TILs of breast cancer tissues may be a valuable biomarker in the development and prognosis of IDC.